if f(x)=2x+1 and g(x)=x^2-7, fing (f-g)(x)

Question

if f(x)=2x+1 and g(x)=x^2-7, fing (f-g)(x)

in progress 0
Remi 7 days 2021-11-25T04:45:52+00:00 2 Answers 0

Answers ( )

    0
    2021-11-25T04:47:12+00:00

    Answer:APEX

    (f-g)(x) = -x^2 + 2x + 8

    Step-by-step explanation:

    0
    2021-11-25T04:47:19+00:00

    Answer:

    (f-g)(x) = -x^2 + 2x + 8

    Step-by-step explanation:

    (f-g)(x) = 2x + 1 – (x^2 -7)

    (f-g)(x) = 2x + 1 – x^2 +7

    (f-g)(x) = -x^2 + 2x + 8

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )